Pediatric endocrinology and growth - Wales, Jeremy K. H; Wit, Jan-Maarten; Rogol, Alan D (W.B. Saunders, 2003)
Third author, Alan D. Rogol, is with Univ. of Virginia, Charlottesville. Previously published as Color Atlas of Pediatric Endocrinology and Growth, text contains color photos illustrating the physical signs and reviews the pathophysiology, differential diagnosis, and treatment for many disorders. Includes growth charts and measurement techniques. Previous edition: c1996.
Keywords: Growth Disorders; Pediatrics; pediatrie; endokrinologie; Endocrinology; poruchy růstu